2006
DOI: 10.1111/j.1365-3083.2006.01753.x
|View full text |Cite
|
Sign up to set email alerts
|

Costimulatory Molecules and Cytokine Production by T Lymphocytes in Common Variable Immunodeficiency Disease

Abstract: Common variable immunodeficiency (CVID) is a heterogeneous syndrome characterized by hypogammaglobulinaemia and recurrent infections. Although early works pointed to a primary B-lymphocyte defect as a cause of the disease, a failure in T-lymphocyte cooperation has also been suggested. T cells exert their costimulatory function through either membrane costimulatory molecules or secreted cytokines, both having an influence in the development of the humoral response. The aim of our study was to evaluate whether a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
15
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 28 publications
7
15
1
Order By: Relevance
“…Recent evidence confirms that IL-4 and IL-10 production and the frequencies of polymorphisms in these genes are comparable with healthy controls, suggesting a minor, if any, role in the pathogenesis of these diseases. 30,[44][45][46][47] Furthermore, CD40 ligand (CD40L/CD154), acting as an important component of the mechanism of Ig production, is normally expressed on stimulated T lymphocytes in a predominant proportion of CVID patients. 45,46,48 Taken together, it appears that the present abnormalities of B-cell differentiation and failure to produce normal amounts of switched immunoglobulin in CVID and IgAD are not due to defect signaling through IL-4, IL-10, or IL-21 and CD40.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence confirms that IL-4 and IL-10 production and the frequencies of polymorphisms in these genes are comparable with healthy controls, suggesting a minor, if any, role in the pathogenesis of these diseases. 30,[44][45][46][47] Furthermore, CD40 ligand (CD40L/CD154), acting as an important component of the mechanism of Ig production, is normally expressed on stimulated T lymphocytes in a predominant proportion of CVID patients. 45,46,48 Taken together, it appears that the present abnormalities of B-cell differentiation and failure to produce normal amounts of switched immunoglobulin in CVID and IgAD are not due to defect signaling through IL-4, IL-10, or IL-21 and CD40.…”
Section: Discussionmentioning
confidence: 99%
“…30,[44][45][46][47] Furthermore, CD40 ligand (CD40L/CD154), acting as an important component of the mechanism of Ig production, is normally expressed on stimulated T lymphocytes in a predominant proportion of CVID patients. 45,46,48 Taken together, it appears that the present abnormalities of B-cell differentiation and failure to produce normal amounts of switched immunoglobulin in CVID and IgAD are not due to defect signaling through IL-4, IL-10, or IL-21 and CD40. Furthermore, the ability to undergo CSR and plasma cell differentiation when stimulated with IL-21, IL-4, and anti-CD40 mAb implies that B cells from patients with CVID or IgAD are not lacking the molecular machinery necessary for such processes.…”
Section: Discussionmentioning
confidence: 99%
“…The allele and genotype frequencies of IFN-γ at position UTR +5644 were similar in the patients and controls. Although a recent study by Pons et al [23] showed a insignificantly higher production of IL-2 and IFN-γ after T-cell stimulation, in our recent study and also in the study by Inoue et al [39], there was no significant difference in the production of these cytokines between patient and control groups. A granulomatous condition, which could lead to a trend to Th1 response, was not detected in our patient group.…”
Section: Discussionmentioning
confidence: 43%
“…There are several studies indicating cytokine production abnormalities in CVID [21,22,23,24]. While cytokine production could be affected by cytokine gene polymorphism, we have genotyped a sample of CVID patients for a number of these cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation